1983
DOI: 10.1097/00006842-198303000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure and Long-Term Practice of the Transcendental Meditation® and TM-Sidhi Program: Effects of TM on Systolic Blood Pressure

Abstract: Systolic blood pressure was measured in 112 subjects practicing the Transcendental Meditation (TM) and TM-Sidhi programs. The subjects were between the ages of 35 and 64 years. A significant difference was found between the systolic blood pressures of subjects (matched for sex, race, and general educational background) practicing the TM and TM-Sidhi programs and norms for the general population. This difference was independent of diet and exercise patterns but related to length of time meditating. A significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…That BP did not drop very much during TM is not surprising, because the subjects (long-term meditation practitioners) already had very low BP for their age (ie, 111.5/74.1 mm Hg), indicating a possible "physiological floor effect." This SBP is 14% lower than the population mean for this age group (129 mm Hg) (30) and is in agreement with previous findings of long-term TM practitioners having lower BP than population norms (8). In this context, it is worth noting that the largest drop in SBP during TM was observed in the subject with the highest BP during eyes-open rest.…”
Section: Tm Vs Relaxation Conditionsupporting
confidence: 91%
See 1 more Smart Citation
“…That BP did not drop very much during TM is not surprising, because the subjects (long-term meditation practitioners) already had very low BP for their age (ie, 111.5/74.1 mm Hg), indicating a possible "physiological floor effect." This SBP is 14% lower than the population mean for this age group (129 mm Hg) (30) and is in agreement with previous findings of long-term TM practitioners having lower BP than population norms (8). In this context, it is worth noting that the largest drop in SBP during TM was observed in the subject with the highest BP during eyes-open rest.…”
Section: Tm Vs Relaxation Conditionsupporting
confidence: 91%
“…Individuals practicing TM have been found to have lower resting SBP and DBP than matched controls (7,8). Recently, studies have reported BP reductions (9,10) as well as reduced cardiovascular disease mortality and total mortality (10-13) with TM.…”
Section: Introductionmentioning
confidence: 99%
“…This pressure is generated by the heart pumping blood around the body and by the resistance of the arteries to the flow of blood 12) . Studies have provided strong evidence that meditation may help decrease BP of the persons who are moderately hypertensive [13][14][15] . Many studies have also revealed that this positive effect disappears when meditation is discontinued 16,17) .…”
Section: Introductionmentioning
confidence: 99%
“…Ruth R.M. et al [26] found that after practice of TM for two years there was no effect on heart rate in his volunteers and therefore he does not support the hypothesis that TM is a state of reduced sympathetic activity. Majority of the workers have shown the significant reduction in resting pulse rate as an effect of meditation and the present study aggress with them.…”
Section: Discussionmentioning
confidence: 83%